Esoteric Everydayness: the Problem of the Occult, Para-psychological, Esoteric, Magical Discourse in Lithuania - Pažėraitė, Aušra Kristina (Religija ir kultūra, 2011)
In this article, the author examines public discourse in Lithuania (of the beginning of twentyfirst century) concerning esoteric, occult, magic, paranormal, psychic phenomena and practices, in the context of formulation some regulatory legislations on their functioning in media. In this examination several categories of opposing these practices and phenomena attitudes have been identified. And finally, have been provided categorization of this type of movements and phenomena in Lithuania in accordance to definitions of esotericism, occultism, and magic, proposed by contemporary researchers in this field of scientific researches.